2009
DOI: 10.1016/j.aprim.2009.05.005
|View full text |Cite
|
Sign up to set email alerts
|

Análisis de las dudas de los médicos de atención primaria

Abstract: The number of doubts that primary care doctor has is relatively small (1.7 for every 10 patients). The most common way to try to resolve them is by referral to a specialist.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 10 publications
0
9
0
2
Order By: Relevance
“…A characteristic feature of primary (PC) surgeries is that they have to attend to a high number of patients suffering from many different health problems, whose clinical complexity is considerable [ 1 , 2 ]. This means that physicians have to deal with several aspects at once, which may raise a multitude of issues in day-to-day clinical practice [ 3 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…A characteristic feature of primary (PC) surgeries is that they have to attend to a high number of patients suffering from many different health problems, whose clinical complexity is considerable [ 1 , 2 ]. This means that physicians have to deal with several aspects at once, which may raise a multitude of issues in day-to-day clinical practice [ 3 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, given that the health system is at saturation point, communication between PC and SC may be difficult, slow, and ineffective [10][11][12][13], and it leads to many referrals to SC (hospitalisation or specialist outpatient clinics). In turn, this leads to excessive delays for appointments [14,15] and to a significant increase in financial, time and psychological costs to physicians and patients. As Horner et al, have pointed out, 65% of referrals are inappropriate and up to 30% of them could be avoided [16].…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that the development of Web 2.0 platforms for communication between care levels enables issues arising in primary care professional practice to be resolved [24]. In this respect, a meta-analysis performed on interactive communication between primary and hospital care physicians in the areas of psychiatry and endocrinology found that this type of communication increased collaboration effectiveness and was associated with important clinical advances in general, and improved patient outcomes in particular [25].…”
Section: Discussionmentioning
confidence: 99%